The International Financial Integration of China and India - Lane, Philip R.; Schmukler, Sergio L. (World Bank, Washington, DC, 2012)
Three main features characterize the international financial integration of China and India. First, while only having a small global share of privately-held external assets and liabilities (with the exception of China's foreign direct investment liabilities), these countries are large holders of official reserves. Second, their international balance sheets are highly asymmetric: both are "short equity, long debt." Third, China and India have improved their net external positions over the past decade although, based on their income level, neoclassical models would predict them to be net borrowers. Domestic financial developments and policies seem essential in understanding these patterns of integration. These include financial liberalization and exchange rate policies, domestic financial sector policies, and the impact of financial reform on savings and investment rates. Changes in these factors will affect the international financial integration of China and India (through shifts in capital flows and asset and liability holdings) and, consequently, the international financial system.